PENYELESAIAN PERKARA TINDAK PIDANA PENYANDANG DISABILITAS ANAK DALAM SISTEM HUKUM PIDANA ANAK DI INDONESIA - Reno Hanggara; Rina Rohayu; Ufran Ufran (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
This research aims to: 1) understand the judicial process for juvenile offenders with disabilities; and 2) examine and analyze the concept of resolving criminal cases committed by juvenile offenders with disabilities in the future. This study is categorized as normative research using a statutory and conceptual approach. The type of data used is secondary data, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection techniques used include literature study and gathering data through electronic media related to the issues being studied. The data analysis technique applied is deductive reasoning, which involves drawing conclusions from general to specific, formulating facts, identifying causes and effects, and reasoning based on case studies. This study concludes that Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (JCJS) serves as a crucial legal foundation for protecting the rights of children in conflict with the law. The JCJS Law provides room for diversion for juvenile offenders with exceptions, namely if the offender is not a repeat offender and the offense is punishable by less than seven years of imprisonment. From a material perspective, the provisions in the JCJS Law do not rigidly explain the rights of children with disabilities when facing the law. The regulations in the JCJS Law still predominantly focus on children with normal physical conditions. From a formal perspective, there is a legal vacuum specifically regulating the rights of children with disabilities in conflict with the law, akin to the regulations for children in conflict with the law under the JCJS Law and for women in conflict with the law under Supreme Court Regulation No. 13 of 2017 on Guidelines for Adjudicating Women in Conflict with the Law. Thus, the judicial process for juvenile offenders with disabilities still applies the normal judicial system as used for other children without disabilities. In the future, if diversion is pursued for resolving criminal cases involving juvenile offenders with disabilities, another alternative for handling such cases is that judges may apply judicial pardon when making decisions. Judicial pardon is regulated under the new Criminal Code in Article 54(2), which provides a normative basis for judges in their decision-making.